A new solar hybrid clean fuel-fired distributed energy system with solar thermochemical conversion. (10th March 2019) - Liu, Taixiu; Liu, Qibin; Lei, Jing; Sui, Jun
Abstract: This paper proposes a new solar hybrid clean fuel-fired distributed energy system to increase the system thermodynamic efficiency and save fossil fuel, in which solar energy is upgraded into high-level chemical energy of syngas (H2 and CO) by integrating solar-driven methanol decomposition based thermochemical conversion. Solar energy, in the form of chemical energy of the generated syngas, is steadily stored and utilized to drive the distributed energy system to generate power, heat and cooling. The double-axis tracking parabolic trough solar collector is deployed to the proposed system to reduce the cosine loss of solar energy. The incorporation of the solar thermochemistry and double-axis solar concentrator technologies leads to a significant improvement in the solar energy utilization efficiency and the off-design performances under varying solar irradiations. With the integration of solar energy utilization and tri-generation, the proposed system achieves a high net solar-to-electric efficiency, 24.66%, and results in high primary energy ratio, 83.86%, exergy efficiency, 38.81%, and carbon emission saving rate, 51.43%. The proposed system is deployed to an office building to study the operation strategies and annual thermo-economy performances, and competitive off-design performances and economy performances are achieved. The research findings open up a new avenue towards the efficient utilization modes of clean fuel and solar energy. Highlights: A new solar thermochemistry-clean fuel hybrid energy system is proposed. Solar energy and clear fuel are efficiently utilized in a cascading manner. Solar energy is upgraded into fuel by the double-axis driven solar thermochemical unit. Competitive thermo-economy performances are achieved.